Metoda wartości uzyskanej jako źródło wiedzy na potrzeby zarządzania przedsięwzięciami informacyjnymi - Dyczkowski, Mirosław (The earned value method as a source of knowledge for it project management, 2005)
The article presents possibilities of application of the Earned Value (EV) method as a source of knowledge for IT project management. In the first part the author briefly characterizes the most important attributes of contemporary IT projects. The next section contains the description of EVA/EVM concept and its application in IT project management. In the third part the author explains the idea of implementation EVA/EVM system as a tool of knowledge acquisition and management in IT projects. The finally section contains few conclusions - the most important is that the EV method can be one of the fundamentals of knowledge based project management (KBPM) concept.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1064, s. 47-57